Strong-field electron emission from gold needle tips - Heimerl, Jonas; Meier, Stefan; Kirchner, Adrian; Weitz, Tobias; Hommelhoff, Peter (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2023)
We show strong-field electron energy spectra from nanometric gold needle tips triggered by femtosecond laser pulses. For this, we use two different wavelengths, 800 nm with 12 fs pulse duration and 1550 nm with 170 fs pulse duration. With an extended plateau and cutoff of rescattered electrons, the recorded electron spectra show the tell-tale features of strong-field physics. Furthermore, the spectra clearly show above-threshold photoemission peaks. Such energy spectra are an ideal tool to benchmark current theory models.
Created from Fastlane, Scopus look-up